Rf-emf exposure measurement for 5g over mm-wave base station with mimo antenna - Wali, Sangin Qahtan; Sali, Aduwati; Allami, Jaafar K.; Faizd, Anwar (Institute of Electrical and Electronics Engineers, 2022)
The fifth-generation (5G) technology offers more capacity and data rates than the previous generations. It provides ultra-low latency and ultra-high dependability, allowing for efficient services in many industries. Using radiofrequency electromagnetic fields (RF-EMF) above 6 GHz in 5G millimeter Wave(mm-Wave) base stations has concerned many people due to the potential health risks caused by EMF exposure. This study aims to measure the maximum exposure emitted by a 5G mm-Wave base station by utilizing international standards in both its assessment methodology and exposure limits. In this study, the R&S Ⓡ TSMA6 scanner, R&S Ⓡ ROMES4 software, and R&S Ⓡ TSME30DC down converter have been used for the measurement campaign; in addition to the user equipment device (UE), GPS, and an omnidirectional antenna. The investigation is based on a code selective method due to the radiated power fluctuations over time with data traffic. To conduct the measurement, six tests are taken based on three different time frames, antenna directions, and user equipment device (UE) to investigate the RF-EMF exposure. The maximum and average exposure from the 5G mm-Wave base station are calculated and compared with the ICNIRP standard. The maximum exposure from the 29.5 GHz base station is found to be 5.71 V/m, and the highest amount of average exposure is 2.02V/m. In this study, it was found that the maximum and average exposure (RF-EMF) produced from a single 5G mm-Wave base station are well within the allowed RF-EMF standard limit.